[Page 16-17] - O Kearnai?, Seaan, 1545?-1587? (My University, 1571)
The first book printed in the Queen Elizabeth Irish type, and the first book to be printed in Ireland in the Irish language.
Aibidil Gaoidheilge & caiticiosma
Bound ca1800 on 6 cords in stained calf; gilt roll along cover borders and turn-ins; gilt fillet on board edges; green, red and white end bands; pink silk marker; marbled endpapers; edges sprinkled blue; later red morocco spine label. Ligatures and contractions on title-page expanded in transcription, in the main following Brian O Cuiv's edition of the work, Dublin 1994, p.51. Printing: woodcut initials A and F are A28a and F28a in M. Pollard, 'The woodcut ornament stocks of the Dublin printers 1551-1700', (FLA thesis 1966); the headpiece used on A1\r, B2\r and F1\r (8 x 56mm.) is not noted by Pollard; all came from the stock of Humfrey Powell, who seems to have ceased printing in 1567. Pollard names the printer of the present work 'The Irish Printer of 1571'. There is evidence that William Kearney, a nephew of John Kearney and a trained printer, was in the trade as early as 1573 (see Dix, Pr. in Dublin prior to 1601, p.19-20). He was later to work in Dublin, from 1592 or 1593, so it is not impossible that he was the printer of the 1571 Aibidil.
Keywords: Irish language -- Alphabet; Irish language -- Orthography and spelling; Church of England -- Catechisms and creeds -- Early works to 1800